2008
DOI: 10.1158/1535-7163.mct-07-0552
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic compounds interfere with chemotherapy of brain tumors due to vessel normalization

Abstract: Glioblastomas are highly aggressive primary brain tumors. Curative treatment by surgery and radiotherapy is generally impossible due to the presence of diffusely infiltrating tumor cells. Furthermore, the blood-brain barrier (BBB) in infiltrative tumor areas is largely intact, and this hampers chemotherapy as well. The occurrence of angiogenesis in these tumors makes these tumors attractive candidates for antiangiogenic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 22 publications
6
78
2
Order By: Relevance
“…This led the authors to conclude that "Vessel normalization has an antagonizing rather than a synergistic or additive effect." 27 Vandetanib is a tyrosine kinase inhibitor with specificity toward epidermal growth factor receptor and VEGF receptor 2, 28 while bevacizumab blocks signaling through VEGF receptor 1 as well as VEGF receptor 2.…”
mentioning
confidence: 99%
“…This led the authors to conclude that "Vessel normalization has an antagonizing rather than a synergistic or additive effect." 27 Vandetanib is a tyrosine kinase inhibitor with specificity toward epidermal growth factor receptor and VEGF receptor 2, 28 while bevacizumab blocks signaling through VEGF receptor 1 as well as VEGF receptor 2.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11]29,30 Although gliomas are certainly at the extreme end of a spectrum with respect to infiltrative growth, it was recently shown that targeting of the angiogenic pathway also in subcutaneous xenografts leads to enhanced invasive growth and metastases. 31,32 Such adverse effects are not expected to occur when directing therapy against the existing tumor vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of phase II studies have now revealed that, despite inducing a radiological response, these inhibitors do not prolong overall survival and allow disease progression, 5,6 likely because diffuse infiltrative growth is angiogenesis independent and provides a mechanism of escape from anti-angiogenic therapies. [4][5][6][7][8][9][10][11] The phenotypic differences that exist in GBM are reflected in the vasculature, which is highly heterogeneous. 12 Vessels may be angiogenic as well as more mature or co-opted, and the latter ones may be unsusceptible to anti-angiogenic therapy.…”
mentioning
confidence: 99%
“…It has often been used as a human glioma model (Claes et al, 2008;Nakatsu et al, 1997). The tumor line expresses several ABC transporters such as P-gp and MRP1 (Rittierodt et al, 2004;Perek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model, normalizing the tumor blood vessel increased topotecan delivery to neuroblastoma (Dickson et al, 2007). However the same strategy (normalizing the tumor blood vessel) does not seem to work for CNS tumor (Devineni et al, 1996b;Claes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%